A filosofia e o filosofar institucionalizado: um olhar sobre o ensino filosófico no ensino médio - Gonçalves, Julio César [UNESP] (2014)
This study aimed to bring the discussion how the philosophy is faring within the bureaucratic institutional body of the school in high school, considering that became mandatory component since 2008. This reflection is justified by the way is our contemporary society (utilitarian and pragmatic) as well as in general education with a focus becomes the formation of a technical knowledge (know-how), so necessary to the existing capitalist system (the prerequisite for selection processes foray into universities - vestibular and ENEM). Therefore the issue that caught my attention among many that underlie the subject of philosophical teaching, and I tried to unveil the following chapters was the philosophy of education limits in high school. Although philosophy have broken the walls of universities and left the shelves of libraries gaining popularity in alternative places, the discussion of his teaching it seemed to me, is not considered a philosophical question but a problem to be discussed between the Education researchers only. To think against the grain of this idea, I return the old discussion of what Kant, Hegel and Nietzsche thought was the philosophy and how to work it in the classroom since to demonstrate that since their times to the present day, there a discussion about the best way to teach it and on which is attributed to Kant the idea of not teach philosophy but philosophy...